Human (in)security and democracy in Central America - O'Brien, Thomas (Taylor & Francis, 2015)
Human security has increasingly shifted attention to the individual, while the state has become guarantor (or violator) of security given its role in governing the domestic environment. This article examines how variations in regime forms influence security, pointing to the importance of political security in the wider human security framework. To illustrate, the article examines the nature of political security in Central America, a region with weakly democratized states and histories of political violence. The findings suggest a link between democracy and human security that is mediated by state capacity and the ability to control non-state violence against individuals.
Keywords: Authoritarian; Contentious Politics; Political Violence; State Capacity